Belize's 2016-17 Sovereign Debt Restructuring : Third Time Lucky? - Asonuma, Tamon (IMF Working Papers; Working Paper ;, 2018)
This paper examines the causes, processes, and outcomes of Belize's 2016-17 sovereign debt restructuring-its third episode in last 10 years. As was the case in the earlier two restructurings, in 2006-07 and in 2012-13, the 2016-17 debt restructuring was executed through collaborative engagement with creditors outside an IMF-supported program. While providing liquidity relief and partially addressing long-term debt sustainability concerns, the restructuring will need to be underpinned by ambitious fiscal consolidation and growth-enhancing structural reforms to secure durable gains.